1975
DOI: 10.1128/jvi.16.6.1401-1408.1975
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T4 baseplate components. II. Binding and location of bacteriophage-induced dihydrofolate reductase

Abstract: The location of T4D phage-induced dihydrofolate reductase (dfr) has been determined in intact and incomplete phage particles. It has been found that phage mutants inducing a temperature-sensitive dfr (dfr-s) produce heat-labile phage particles. The structural dfr produced by these ts mutants was shown to assume different configurations depending on the temperature at which the phage is assembled. Morphogenesis of incomplete phage particles lacking the gene 11 protein on their baseplates was found to be inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…It seems likely, therefore, that structural DFR is associated with wedges. This is not unexpected, since both we and Kozloff et al (12,26) have shown that structural DFR is partially covered in the baseplate by gpll, a known constituent of wedges. DISCUSSION This study has revealed the following.…”
Section: Fig 3 Specificity Of the Double Antibody Precipi-supporting
confidence: 71%
See 2 more Smart Citations
“…It seems likely, therefore, that structural DFR is associated with wedges. This is not unexpected, since both we and Kozloff et al (12,26) have shown that structural DFR is partially covered in the baseplate by gpll, a known constituent of wedges. DISCUSSION This study has revealed the following.…”
Section: Fig 3 Specificity Of the Double Antibody Precipi-supporting
confidence: 71%
“…Kozloff et al demonstrated DFR enzyme activity in disrupted baseplates (18), albeit at low levels. It was reported subsequently that defective virions missing the baseplate proteins gp 11 and gp 12 (products of genes 11 and 12) needed no artificial disruption to demonstrate detectable levels ofDFR activity (26) or ofthymidylate synthetase activity (16). Our laboratory and that of Kozloff showed that antisera prepared either to purified DFR (24) or to thymidylate synthetase (2) neutralize T4 infectivity, thus indicating the presence of these antigens in the virion.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Note also that two point mutants in the frd gene also form this cross-reacting material. One of these, frdll, is an amber mutant, but, evidently, it synthesizes an incomplete polypeptide nearly as long as the wild-type protein (17). These observations involve us in the same apparent paradox as do our similar experiments with thymidylate synthetase antiserum: mapping data indicate the presence of long 4.…”
Section: 8mentioning
confidence: 51%
“…This paper gives the detailed properties of these two mutants and presents additional evi-dence that the td gene product is a tail plate component adjacent to the dfr in the tail plate. A tentative scheme for the structural relationships of the tail plate folate (14), dfr (12), and td is proposed.…”
mentioning
confidence: 99%